Efforts to Improve Basic Long Serve Skills in Badminton Learning Through the Inquiry Method - Fikri, Izzul; Anam, Khoerul; Suganda, Mikkey Anggara (Jurnal Ilmu Keolahragaan, 2023)
This study aims to determine the level of basic long service skills in badminton among students at MTs Al Anwar Sampiran, Talun District, Cirebon Regency. This study was motivated by the low level of basic long service skills among students, which are an important foundation in badminton. The method used was a descriptive quantitative approach with data collection techniques in the form of long service skill tests. The research subjects consisted of 51 students who participated in badminton extracurricular activities, with sampling using cluster random sampling techniques. The data were analysed using descriptive statistics and frequency distribution. The results showed that, in general, the students' basic long service skills were in the ‘moderate’ category, with a percentage of 33.33%. Among male students, most were in the ‘moderate’ (30.77%) and “good” (26.92%) categories, while among female students, the majority were in the ‘moderate’ category (60.00%). Factors affecting these results include irregular attendance at training sessions and a lack of discipline among students in following the extracurricular schedule. The conclusion of this study shows that the intensity and consistency of training are important factors in improving basic long service technical skills. Therefore, a more structured coaching and training strategy is needed, both through school activities and training sessions.